The perilous consequences of bowel preparation: a case study with literature review of Boerhaave syndrome - Gao, Ruo-yu; Wei, Xiao-lan; Wu, Jin-feng; Zhou, Zhi-wei; Yu, Xi-qiu (Frontiers in Medicine, 2024)
Colonoscopy is widely acknowledged as a prevalent and efficacious approach for the diagnosis and treatment of gastrointestinal disorders. In order to guarantee a prosperous an effective colonoscopy, it is imperative for patients to undergo an optimal bowel preparation regimen. This entails the consumption of a substantial volume of a non-absorbable solution to comprehensively purge the colon of any fecal residue. Nevertheless, it is noteworthy to acknowledge that the bowel preparation procedure may occasionally elicit adverse symptoms such as nausea and vomiting. In exceptional instances, the occurrence of excessive vomiting may lead to the rupture of the distal esophagus, a grave medical condition referred to as Boerhaave syndrome (BS). Timely identification and efficient intervention are imperative for the management of this infrequent yet potentially perilous ailment. This investigation presents a case study of a patient who developed BS subsequent to the ingestion of mannitol during bowel preparation.Furthermore, an exhaustive examination of extant case reports and pertinent literature on esophageal perforation linked to colonoscopy has been conducted. This analysis provides valuable insights into the prevention, reduction, and treatment of such serious complications.